Air quality and health impact of cement industry on urbanized rural areas - Karam, Gebran (2011)
Criteria air pollutants: PM10, CO, SO2 and NO2, as well as general meteorological conditions were monitored for the first time ever at five locations in and around the cement industry zone situated in Northern Lebanon in and around the town of Chekka. Two Environmental Monitoring Stations were deployed to survey five locations for intermittent periods of two weeks each from December 2002 to January 2004. Data collected showed that EPA air quality standard levels of SO2, and PM10 were exceeded in more than one location and for long periods of time during the dry season. Levels and locations of measured pollutants were in agreement with the dominant wind directions, and the meteorological conditions. Numerical modeling using CALPUFF allowed the development of scenarios for the fate and transport of smoke stack emissions. Results have confirmed that the industrial plants smoke stacks do not account for more than 10 to 20% of the measured levels of SO2 and PM10. The rest is attributed to secondary sources at the mills, quarries, and the private power plants operating within the industrial compounds. The health impact on the immediately exposed population was estimated. The different stakeholders were engaged in a series of facilitated meetings which resulted in the creation of a first of a kind tri-partite environmental partnership between local municipalities, the industry, and the Ministry of the Environment for the management of air pollution.